Exploitation of dancing boys in Afghanistan: a tragic reality / Norashikin Shariffuddin and Leviana Andrew - Shariffuddin, Norashikin; Andrew, Leviana (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The phenomenon of exploiting young male dancers in Afghanistan, known as bacha bazi, has long been a source of concern, raising important issues with the rights and safeguarding of minors. Despite the challenges, there is cause for optimism and a more promising future through the enforcement of legal protections and the collective endeavours of the entire community to combat this abhorrent practice. (Borile, 2019; Essar et al., 2021). The objective of this article is to share the dark reality of bacha bazi in Afghanistan, together with the existing legal system designed to safeguard them and the urgent need for greater intervention to end it. Bacha bazi, a deeply rooted cultural practice in Afghanistan, has transformed into a kind of exploitation where juvenile boys are forced to perform dances for the entertainment of adult guys. According to Noman (2016), this type of exploitation often involves sexual abuse, acts of violence, and disregard for the basic rights and dignity of these vulnerable children. They are deprived of their childhood, exposed to physical and emotional stress, and denied protection and stability. Further, this exploitative practice of bacha bazi enables abusers to avoid being held responsible.